Investigation of Mixed Convection in a Cylindrical Lid Driven Cavity Filled with Water-Cu Nanofluid - Amirreza Niazmand; Jalal Fathi Sola; Farhad Alinejad; Foad Rahimi Dehgolan (Inventions, 2019)
The present numerical research studies the effect of nano-materials in a lid-driven cylindrical cavity with rotation of circumferential top wall. The heat is transferred from two lateral walls to the domain by constant temperature conditions while other walls are kept isolated. The non-dimensional equations are solved by Finite Volume Method (FVM) and SIMPLEC method. The effect of Reynolds (Re = 100, 400, 1000), Ryleigh (Ra = 104, 105, 106) numbers are studied. In addition, the effect of concentration of nano materials ( <semantics> ϕ </semantics> = 0%, 1%, 5%), the Height Ratio (HR = 1, 0.5, 2) on Nusselt number, isotherm lines and streamlines are studied. The results show that Reynolds number also can change the effect of nano particles on the heat transfer rate. It is observed that the height ratio increase can improve the Nusselt number since the number and the size of vortices inside the cavity changes. In addition, increase of Ra number can change the flow structure inside the cavity which can help in increasing of Nusselt number.